Overcoming barriers to proactive plastic recycling toward a sustainable future - Andrew Chapman; Kanchan Kumar Sen; Takako Mochida; Yuuki Yoshimoto; Koki Kishimoto (Environmental Challenges)
The plastics sector, accounting for a significant portion of global emissions, presents a challenge and an opportunity in achieving carbon neutrality. Despite Japan's commendable polyethylene terephthalate (PET) bottle recycling rates, most plastics are thermally recycled, creating environmental issues. This study proposes an evaluation framework to enhance recycling, aligned with end-user preferences and fostering a circular plastics economy. Employing a mixed-methods approach, this study conducts fieldwork including interviews with plastic recyclers and analysis of industry data. A weighted sum multicriteria analysis integrating end-user preferences, recycling effectiveness, and market dynamics is utilized. Systemic, process, and policy challenges were shown to hinder sustainable recycling practices, while varying willingness to pay, emission and cost reduction potentials, among acceptability and sectoral diversity informed priority plastic types for recycling. Multicriteria analysis showed that although PET is favored by end users, Polyoxymethylene (POM) emerges as a potential priority target for manufacturers and recyclers. Sensitivity analysis underscores the potential impact of establishing or enhancing willingness to pay (WTP) toward certain plastic types. Moreover, manufacturer and recycler evaluations suggest a broader willingness to recycle plastics than previously assumed. The proposed evaluation framework offers insights toward plastic recycling strategies. Policy interventions such as sustained subsidies for recyclers, market incentives leveraging WTP preferences, and technological advances, including chemical recycling and the broadening of plastic type recycling in line with user and manufacturer preferences, could all contribute to promoting sustainable plastic recycling practices.